Chemical characterization, adverse effects and potential toxicological effects of medical devices applied in gastrointestinal disease: a review - Varthya, Shoban Babu; Krishna, Hare (International Journal of Basic & Clinical Pharmacology, 2021)
Medical devices have gained popularity as a therapeutic or diagnostic purpose in gastrointestinal obstructions caused by malignant tumour or benign stricture or any other pre-existing conditions. The problems of stents are like sense of foreign body, migration or incomplete expansion or re obstruction. In this scenarios, self-expandable metallic stents (SEMS), or biodegradable self-expanding stents, wall flex stents, drug eluted stents, etc prevents the obstruction related difficulties. SEMS associated with re-obstruction and migration along with difficulty in removal and chances of leaks due to corrosion. In case of biodegradable self-expanding stents, which are either made of magnesium-based materials or synthetic polymers, such as polylactide or polyglycolide, or co-polymers, such as polydioxanone. Magnesium-based materials are very biocompatible but due to the property of dissolving in the body by rapid corrosion, degradation can occur before the therapeutic objective is reached. Synthetic polymers associated severe mucosal hyperplastic reaction with overgrowth and/or ingrowth. Wall flex stents, drug eluted stents can be used to prevent complications associated with above variants but their clinical significance and toxicological effects were not evaluated completely. Under this given scenario toxicological evolution of various medical devices used in gastrointestinal disease and their potential toxicological effects are required to understand their tolerability and acceptability.